Troubleshooting Analog Circuits - Pease, Robert A. (Newnes [Imprint] San Diego : Elsevier Science & Technology Books, 1991)
Annotation Based on the author's popular series in EDN Magazine, the book contains a wealth of information on debugging and troubleshooting analog circuits. In this book, you'll find advice on using simple equipment to troubleshoot (would you believe an ordinary AM radio?); step-by-step procedures for analog troubleshooting methods; and generous helpings of the author's unique insights, humor, and philosophy on analog circuits.*Provides proven methods for troubleshooting analog circuits
Scholarly & Professional